Homoerotismo em questão na literatura brasileira – a condição homoafetiva nas obras Stella Manhattan e Keith Jarret no Blue Note: improvisos de jazz de Silviano Santiago - Alves, Álisson de Albuquerque (2010)
The literature is a propitiate way so that several speeches, beyond what is said about the own literary phenomenon, be presented/recreated in the sense of envision possibilities of reconstruction/reframing of the subjects in the cultural space, once these ones can, on one side, make part and/or to understand the status quo hegemonic, as well as they can, on the other hand, accomplish, with effect, the (re)appearance of new "individual" subjects - ethnic minorities and class, nationals and gender -, which insist in a fight -demarcate territories and to look for the recognition of cultural values that should be given. For this optics, we left from the literary production of representation homoerotic that, as the feminine representation, it works a speech appraiser of the condition of the gay subjects in the sociocultural context, mainly when it is taken into consideration that these suffer, as it discusses Silva (2007), the prejudice, the homophobia or intolerance. Then, with base in what seems be the most important criterion to consider the existence of a literature of gay expression - the homoerotic thematic, we had the objective, in that master's degree dissertation, to observe and to discuss the representations homoerotic, analyzing the condition homoaffective in the novel "Stella Manhattan" (1991) and the book of short stories "Keith Jarret no blue note" (1996), both by Silvano Santiago, with the intention of verifying the representations of the homoerotic desire, as well the aspects that, hypothetically, could make possible the constitution of a "gay aesthetics", according to the thought of some theoretical as Wilton Garcia (2000, 2004), for example, have been enough to deconstruct the duality homoaffective that ranging from the practice of homosexual and heterosexual and homophobic and makes the expression of gay desire a possibility of institutionalization of the gay in the context sociocultural and construction of "identity". So, I intend this work to establish a link between what is conventionally known as gay literature, considering its existence, and how the homoerotic themes and recurring elements of this literature are approached in works that we proposed to examine. For this, we will take as reference some texts that talk about the aspects of the conceptual issues and historical notions of gender, sexuality and homoeroticism, the questions surrounding the relationship between literature and homoeroticism, considering the erotic aspect of the term. Finally, the “identity” / sexual homoerotic through a wide study on the expression of gay literature, and later through the works that are part of our corpus analysis – “Stella Manhattan” (1991) and book of short stories "Keith Jarrett on Blue Note" (1993), both of Silvano Santiago.